Cooperative Group Work as a Flexible Learning Strategy of the 4th Year College Students of MSU-Sulu - Omar, Andrada Ajijul (HM Publisher, 2022)
The education system has been shaken by an unprecedented health crisis. Various governments around the world have launched civic response efforts to mitigate the negative impact of the pandemic on education. Due to the movement and health protocol restrictions, the current situation may exacerbate the difficulty encountered during online learning. Teachers must take a different approach to learn in this situation. To improve learning, teachers must assist students and manage them. Teaching is most effective when the learner actively participates and cooperates. Through systematic classroom interaction, cooperative group work as flexible learning allows students to support and encourage one another. This study was conducted at MSU-Sulu on cooperative group work as an approach. The study's participants are 4th year College education students. The researcher used a checklist questionnaire to determine the potential effects of cooperative group work as flexible learning. The scoring scheme employed 4 points Likert scale. The findings of the study on the effects of cooperative group work on the performance of 4th year college education students. On the potential effects of cooperative group, workshop participants agreed. Students should be encouraged to adopt cooperative group work to enhance their knowledge and skills, especially during a pandemic. Teachers must ensure that this approach is used in learning sessions because it equates to improvement in students' academic performance.